What Is and Isn't a Pesticide? - Frederick M. Fishel (EDIS)
The Federal Fungicide, Insecticide and Rodenticide Act (FIFRA) defines pesticides. Some substances might appear at first to be classified by FIFRA as pesticides, but this is not necessarily the case. This document will discuss FIFRA's criteria for determining what is and is not considered a pesticide. This document is PI-96, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date January 2006.